Permainan Bola Basket Modifikasi, Strategi Pembelajaran Inovatif Untuk Meningkatkan Ketrampilan Variasi Dan Kombinasi Gerak Dasar Dalam Permainan Bola Besar Sederhana di MIN 2 Pemalang (BEST PRACTICE) - Ibrohim, Ahmad (Indonesian Journal of Islamic Elementary Education, 2022)
A teacher who delivers teaching with good and innovative strategies, will create an interesting learning atmosphere and also improve the skills of students.This studyaims to provide information on the application of modified basketball games as an innovative learning strategy that can improve basic movement variations and combination skills in simple big ball games at MIN 2 Pemalang. This research was conducted in August 2022 with the best practice method in the learning process that was carried out in August 2022 at Madrasah Ibtidaiyah Negeri 2 Pemalang. Best Practice is the "Best Practice" of the success of a teacher or group of teachers in carrying out their duties, including in overcoming various problems in their school (Kemendikbud, 2016). While the data collection is done through literature study and direct observation where the author is directly involved in the program.results of this study can be understood that the number of students' scores using learning modifications is 2485 withan average value of 82.83 and not using Learning Modifications in basketball games, the total score is 2295 and the average value is 76.50 . The percentage of students' scores using incomplete learning modifications is 3.33%, according to the KKM of 10% and above the KKM of 86,66% while the percentage of students' scores by not using incomplete learning modifications is 33.33%, according to the KKM of 13.33% and above the KKM by 53.33%.Taken together, these results will provide information that the application of innovative learning strategies in modified basketball games can improve students' learning skills.